2017
DOI: 10.1002/2016jc012339
|View full text |Cite
|
Sign up to set email alerts
|

Upper ocean observations in eastern C aribbean S ea reveal barrier layer within a warm core eddy

Abstract: Three‐dimensional measurements of a large warm core eddy (WCE) and the Caribbean Current are acquired using oceanic profilers deployed during a NOAA research aircraft study in September 2014 in the eastern Caribbean Sea. Measurements of the near‐surface atmosphere are also collected to examine air‐sea processes over the eddy. These novel measurements showcase temperature and salinity for the eddy and background flow, upper ocean stratification, a residing barrier layer (BL), velocity structure, and water mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
21
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 56 publications
(114 reference statements)
10
21
2
Order By: Relevance
“…The thickest layers were observed within the core and at the periphery of the anticyclone (BLT = 35±1 dbar). This is in line with observations of Rudzin et al (), who found thicker barrier layers inside than outside their surveyed anticyclone.…”
Section: Upper Ocean Characteristicssupporting
confidence: 94%
See 3 more Smart Citations
“…The thickest layers were observed within the core and at the periphery of the anticyclone (BLT = 35±1 dbar). This is in line with observations of Rudzin et al (), who found thicker barrier layers inside than outside their surveyed anticyclone.…”
Section: Upper Ocean Characteristicssupporting
confidence: 94%
“…The anticyclone originated near Grenada Passage, which is similar to the anticyclone surveyed by Rudzin et al (). Based on the low salinity and elevated silicate concentrations in the core of the anticyclone, we suggest that the anticyclone entrained surface waters originating from the Orinoco River.…”
Section: Summary Discussion and Conclusionsupporting
confidence: 83%
See 2 more Smart Citations
“…Eddies such as the anticyclonic features associated with North Brazil Current Rings eventually carry freshwater, originating from the Amazon/Orinoco river, into the region. Linkages between the freshwater surplus by the rivers and intensification of storms and cyclones have been reported for the large scale (Reul et al 2014) and for the region east of the Antilles, in the Caribbean, for individual eddies (Rudzin et al 2017).…”
Section: Ocean Eddiesmentioning
confidence: 99%